Alcohol Consumption Does not Impede Recovery from Mild to Moderate Traumatic Brain Injury. (18th August 2016) - Silverberg, Noah D.; Panenka, William; Iverson, Grant L.; Brubacher, Jeffrey R.; Shewchuk, Jason R.; Heran, Manraj K.S.; Oh, Gary C.S.; Honer, William G.; Lange, Rael T.
Abstract: Objectives: To examine the effect of pre-injury alcohol use, acute alcohol intoxication, and post-injury alcohol use on outcome from mild to moderate traumatic brain injury (TBI).Methods: Prospective inception cohort of patients who presented to the Emergency Department with mild to moderate TBI and had a blood alcohol level (BAL) taken for clinical purposes. Those who completed the 1-year outcome assessment were eligible for this study ( N =91). Outcomes of interest were the count of post-concussion symptoms (British Columbia Post-Concussion Symptom Inventory), low neuropsychological test scores (Neuropsychological Assessment Battery), and abnormal regions of interest on diffusion tensor imaging (low fractional anisotropy). The main predictors were pre-injury alcohol consumption (Cognitive Lifetime Drinking History interview), BAL, and post-injury alcohol use.Results: The alcohol use variables were moderately to strongly inter-correlated. None of the alcohol use variables (whether continuous or categorical) were related to 1-year TBI outcomes in generalized linear modeling. Participants in this cohort generally had a good clinical outcome, regardless of their pre-, peri-, and post-injury alcohol use.Conclusions: Alcohol may not significantly alter long-term outcome from mild to moderate TBI. ( JINS, 2016, 22, 816–827)